The Players' Realm: Studies on the Culture of Video Games and Gaming - Williams, James Patrick; Smith, Jonas Heide (McFarland, 2007)
"This study sketches some of the various trajectories of digital games in modern Western societies, looking at the growth and persistence of the moral panic that continues to accompany massive public interest in digital games. The book continues with a new phase of games research exemplified by systematic examination of specific aspects of digital games and gaming"–Provided by publisher.
OCLC: 700517982
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Autrice; _Nettoyé